2014
DOI: 10.3346/jkms.2014.29.2.254
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enzyme Replacement Therapy on Linear Growth in Korean Patients with Mucopolysaccharidosis Type II (Hunter Syndrome)

Abstract: Hunter syndrome (or mucopolysaccharidosis type II [MPS II]) arises because of a deficiency in the lysosomal enzyme iduronate-2-sulfatase. Short stature is a prominent and consistent feature in MPS II. Enzyme replacement therapy (ERT) with idursulfase (Elaprase®) or idursulfase beta (Hunterase®) have been developed for these patients. The effect of ERT on the growth of Korean patients with Hunter syndrome was evaluated at a single center. This study comprised 32 patients, who had received ERT for at least 2 yr;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
1
21
0
1
Order By: Relevance
“…17 The literature search identified 24 additional studies having some quantitative data on 12 outcomes of ERT ( Table 1). Studies variably enrolled patients with only attenuated MPSII, [17][18][19][20][21][22][23][24][25] both phenotypes, 23,[26][27][28][29][30][31][32][33][34][35] and only the severe phenotype. [36][37][38] Only one study 39 and the RCTs 17,20 had a control group; many results describe changes in outcome measures from study baseline to endpoints.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The literature search identified 24 additional studies having some quantitative data on 12 outcomes of ERT ( Table 1). Studies variably enrolled patients with only attenuated MPSII, [17][18][19][20][21][22][23][24][25] both phenotypes, 23,[26][27][28][29][30][31][32][33][34][35] and only the severe phenotype. [36][37][38] Only one study 39 and the RCTs 17,20 had a control group; many results describe changes in outcome measures from study baseline to endpoints.…”
Section: Resultsmentioning
confidence: 99%
“…23,25,27,30 Eight studies variably reported actual height, growth velocity, or standardized measurements (z-score normalized for age and sex). 19,[23][24][25]27,30,35,39 Five studies reported data in age-adjusted z-scores; 23,27,30,35,39 only one 39 had an untreated control group ( Supplementary Table S9). ERT did not reverse the downward trend, but appeared to result in a less steep decline in age-adjusted height.…”
Section: Growth: Heightmentioning
confidence: 99%
“…Short stature is a prominent and consistent feature in MPS type II. The effect of ERT on the growth of 32 Korean patients with Hunter syndrome was evaluated at a single center (11); the patients had marked retardation of growth as they grew older. However, ERT may have less of an effect on the growth of patients with the severe form of Hunter syndrome.…”
Section: An Animal Model Of Mpsmentioning
confidence: 99%
“…Significant increases in height and weight observed during the study were regarded as normal growth velocity in this age population. Previous studies reported a positive effect of ERT in children with Hunter syndrome [22,23]. However, continuous follow-up is needed to evaluate the long-term effects of ERT on the growth of Hunter syndrome children.…”
Section: Discussionmentioning
confidence: 94%